The MRZ reaction in primary progressive multiple sclerosis. Issue 1 (December 2017) - Hottenrott, Tilman; Dersch, Rick; Berger, Benjamin; Rauer, Sebastian; Huzly, Daniela; Stich, Oliver
Abstract Background The MRZ reaction (MRZR), composed of the three antibody indices (AI) against measles, rubella and varicella zoster virus and found positive in the majority of relapsing-remitting multiple sclerosis (RRMS) patients, is absent in other inflammatory neurological diseases (OIND). So far, it has been uncertain whether its differential diagnostic promise extends to patients with primary-progressive multiple sclerosis (PPMS). Objective To investigate the prevalence of MRZR in PPMS compared to RRMS and OIND patients. Methods MRZR was assessed in patients with PPMS (n = 103), RRMS (n = 100) and OIND (n = 48). Both stringency levels for MRZR testing, MRZR-1 (≥1 AI positive) and MRZR-2 (≥2 AI positive), were applied. Results Prevalence of positive MRZR-1 was 83.5% in PPMS and 67.8% in RRMS (p < 0.05). A positive MRZR-2 was found in 54.4% of PPMS and in 43.0% of RRMS patients (not significant). Compared to both MS subgroups, OIND patients exhibit lower frequencies of positive MRZR (MRZR-1: 22.9%, MRZR-2: 8.3%; p < 0.0001 each). Conclusion Positive MRZR was at least as frequent in PPMS as in RRMS and much less frequent in OIND, confirming its promise as a potentially useful diagnostic tool for distinguishing both MS course types from OIND.